Cost-effectiveness of oil and milk fortification by scale for reducing Vitamin A and Vitamin D deficiency in India - Abhishek Kumar; Komal Ahluwalia; Anirudhan P. Edathil; Rajan Sankar; Nimmathota Arlappa; Sirimavo Nair; Mona Duggal; William Joe (PLoS ONE, 2025)
Background Although broad-scale data might suggest low prevalence, millions of children in India still suffer from Vitamin A and Vitamin D deficiencies despite India’s existing guidelines for Vitamin A deficiency. To address the issue, the Government of India has recommended fortification of oil and milk to improve Vitamin A and Vitamin D consumption. However, there is limited information on the health benefits and cost-effectiveness of fortifying oil and milk at scale. Objective To estimate the health benefits and cost-effectiveness of supplementation programme and fortification of milk and oil among children under 5 years, pregnant women, women in the reproductive age group, and the elderly. Data and methods To measure the health benefits associated with supplementation and fortification of oil and milk, the number of DALYs that are currently lost due to Vitamin A and Vitamin D deficiencies were estimated. For Vitamin A related mortality, a reduction of 4%, 12% and 23% were assumed while the assumptions for estimating morbidity benefits were derived from Global Burden of Disease. For the costing exercise, we considered the following two scenarios: (1) high-dose vitamin A supplementation for children and pregnant women; (2) industrial fortification of oil for children, pregnant women, women in the reproductive age group, and the elderly. Results Overall, intervention related to Vitamin A could avert 1,119,044 Years of Life Lost (YLLs) at a 23% reduction, 194,616 YLLs at 4%, and 583,849 YLLs at 12% and 28,534 YLDs. Intervention related to Vitamin D could avert 99,219 YLDs. The total cost for supplying supplements to approximately 109,965 thousand children and 26,920 thousand pregnant women is around 26 million USD. The cost to fortify is 7.6 million USD for oil and 9.8 million USD for milk fortification for children and women. The overall cost effectiveness ratio of the fortification programme is 150. Conclusion Fortification could emerge as a potentially superior long-term solution, considering the widespread consumption of oil and milk, offering a broader reach to the population.